A Single-Mode 852-nm Faraday Laser - Zhiyang Wang; Zijie Liu; Jianxiang Miao; Hangbo Shi; Xiaomin Qin; Xiaolei Guan; Jia Zhang; Pengyuan Chang; Tiantian Shi; Jingbiao Chen (IEEE Photonics Journal)
Realizing always atomic translation frequency output, single-mode, high frequency stability, narrow linewidth semiconductor lasers, is one of the ultimate visions of areas related to quantums, such as quantum precision measurement and atomic physics. A single-mode Cs atom 852 nm Faraday laser, utilizing a corner cube retroreflector as the feedback element, is demonstrated and termed as a corner-cube-feedback Faraday laser. Its output frequency remains close to the Cs atomic Doppler-broadened transition line, and through the optimization of the working parameters of Faraday anomalous dispersion optical filter (FADOF), the laser output mode can still remain single, even though the diode current changes from 55 mA to 155 mA (with incremental step of approximately 2 mA) and the diode working temperature varies from $11.8 \,\mathrm{^{° }C}$ to $37.2 \,\mathrm{^{° }C}$ (with incremental step of approximately $3.5 \,\mathrm{^{° }C}$ ). Also, the single-mode laser oscillation can be achieved over a substantial angular range, specifically between +3 $\mathrm{^{° }}$ and −3 $\mathrm{^{° }}$ , where the angle is defined as the deviation of the incident light from the optical axis of the corner cube. Using the corner-cube retroreflector as external cavity feedback element, the environmental compatibility and reliability can be improved due to the precise reflection of the incident light beam back to its original direction. The most probable linewidth is 8 kHz measured by heterodyne beating with two identical lasers. The output power can achieve a maximum of 57 mW at 155 mA. As for the noise performance of the laser, the typical value of relative intensity noise (RIN) at 10 kHz is lower than −134 dBc/Hz. The pahse noise of the laser is superior than the commerical product. This single-mode corner-cube-feedback Faraday laser can be widely used in quantum precision measurement, such as atomic clocks, atomic gravimeters, and atomic magnetometers, etc.